Solutions for Developing S&T Human Resources: The Foundation for Sustainable Development - Thuy, Dao Thi Thu (VNU Journal of Science: Policy and Management Studies, 2020)
The world is moving towards a knowledge-intensive economy, enhancing cooperation and competition in science and technology. In the knowledge economy, the research, development and commercialization of science and technology products are becoming increasingly important. Put economic development and human development in relation to sustainable development goals, human development - human development is both the driving force and the goal of socio-economic development. and environment. In fact, it is necessary to have stronger and soldier measures to promote the development of S&T human resources in Vietnam. Since then, thoroughly utilize the achievements of modern science and technology, improve the competitiveness of Vietnam's economy and position in the international arena, especially in the trend of sustainable development. - the general trend that all humanity is striving towards.